2013
DOI: 10.4236/ojst.2013.32035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 4 different bone graft substitutes and autogenous bone grafting in root-end resection osteotomies after retrograde root-filling with Intermediate Restorative Material (IRM): An experimental study in dogs

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The histomorphometric analysis in the present study revealed that the bone volume value in the osseous defects filled with PTG was higher than those occupied with Nanobone® but no statistically significant difference could be detected between the two groups. This agreed with Wälivaara and Abrahamsson in 2013 (18) where no statistically significant difference could be detected between autogenous bone or one of the bone graft substitutes, when they were used to fill osseous defects in dogs following apicectomy of mandibular premolars. This non -significant difference might be explained by sample size limitation.…”
Section: Discussionsupporting
confidence: 88%
“…The histomorphometric analysis in the present study revealed that the bone volume value in the osseous defects filled with PTG was higher than those occupied with Nanobone® but no statistically significant difference could be detected between the two groups. This agreed with Wälivaara and Abrahamsson in 2013 (18) where no statistically significant difference could be detected between autogenous bone or one of the bone graft substitutes, when they were used to fill osseous defects in dogs following apicectomy of mandibular premolars. This non -significant difference might be explained by sample size limitation.…”
Section: Discussionsupporting
confidence: 88%
“…Histological specimens were evaluated qualitatively and semi‐quantitatively on the basis of established scoring methods in bone histology and pathology or own published methods as well as methods from the literature on certain parameters investigated in similar studies on the healing of bone replacement materials . The assessment was always performed in a blinded way by two independent, histologically experienced examiners on three different sections of the section series (central, lateral).…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of osteogenesis was assessed semi-qualitatively using the following scoring system: 0 = no features of osteogenesis; 1 = bone formation around graft (e.g., granules) with the appearance of osteoblasts and deposition of osteoid; 2 = bone formation around graft with primary bone features; 3 = bone trabeculae formation around grafts with features of active remodeling (detection of lamellar bone with primary osteons and osteocytes, vascular detection, fibrous bone remnants in the lamellar bone, and remains of bone replacement nanomaterial embedded in/on the bone); 4 = mature lamellar bone with osteons [14]. In addition, the immune reaction to NG was assessed using a semi-quantitative score according to the following scheme: 0 = none; 1 = loose infiltrates, disseminated or focal; 2 = dense, moderately extensive lymphocytic infiltrates; 3 = extensive, dense lymphocytic infiltrates with edema and focal giant cells; 4 = pronounced inflammatory reaction including giant cells and necrosis [27]. The assessment was performed by two independent observers blindly…”
Section: Histological Evaluation Of Bone Augmentation With Ha/β-tcpmentioning
confidence: 99%